Color Source for the First Argentinian Flags - Picone, Andrea Lorena (2019)
In this work, a historical controversy of more than 200 years is settled by the study of the oldest preserved Argentinian flag. The results of the present work reinforce the hypothesis of a number of historians who consider it to be the first flag that was originally hoisted on February 27, 1812, on the banks of the Paraná River. The work consists of a study of the original textile. Through chemical analysis and implementation of different types of analyses, techniques, and spectroscopies such as UV−vis, UV−vis diffuse reflectance spectroscopy, attenuated total reflectance Fourier transform infrared spectroscopy, scanning electron microscopy−energy-dispersive X-ray spectroscopy, and resonance Raman, the original characteristics of the flag of Macha were determined. The flag was colored with indigotin from Europe (from Isatis tinctoria) and made of silk; it is white, blue, and white in a horizontal arrangement. It was not treated with tin, and its blue color was subsequently adopted by the Central American Confederation and later by various states of Central America. According to related contemporaneous stories, its preservation was due to the watchfulness of the patriots.